Causes of crane accidents at construction sites in Malaysia - Abdul Rahim, A. H.; Ridzuan, Azhari; Rozana, Zakaria; Eeydzah, Aminudin; Putra Jaya, Ramadhansyah; Logeswaran, Nagarajan; Khairulzan, Yahya; Zaiton, Haron; Riduan, Yunus (IOP Publishing, 2019)
The usage of crane in the construction industry is widespread and very important regardless of the project size. In tall building construction, the efficiency of the tower crane is the backbone of the project success. The crane operator is responsible to control the crane efficiently and follows the provided safety guidelines. Loss of life, injury, and property damages are the consequences that will happen if the requirements and procedures for crane handling are not properly done. The increasing number of crane accidents in Malaysia has driven the awareness to conduct this study as to avert this problem from occurring. Thus, this study was conducted to analyse crane's accident statistic at construction sites in Malaysia. This study utilises official crane accident report database and document search from the Department of Occupational Safety and Health (DOSH). All collected data were analysed using two methods, namely frequency analysis and content analysis. The results of the study show that, mobile crane recorded 23 numbers of crane accident cases and the highest in term of the type of cranes. Structural failure leads as a higher factor that contribute to crane accident in Malaysia with 28 counts of causes. In order to minimize crane accidents, crane's safety measure and procedure as well as proper training to crane operator are among potential ways.